PREDIKSI PENGANGKATAN KARYAWAN DENGAN METODE ALGORITMA C5.0 (STUDI KASUS PT. MATARAM CAKRA BUANA AGUNG) - Ismasari Nawangsih; Sifa Fauziah (Jurnal Pelita Teknologi, 2021)
In the decision to appoint permanent employees that can be made at the company is determined in terms of attendance and good discipline. Determination of the appointment of permanent employees at PT. Mataram Cakra Buana Agung still looks imprecise and takes a long time. Then a study was conducted that aims to determine the prediction information on permanent employee appointments by looking at the criteria set by the company using the C5.0 classification algorithm with the decision tree method. The data used in this study are employee data owned by PT. Mataram Cakra Buana Agung as many as 403 data, the process of testing the method using Rapid Miner9.5. Based on the results of testing on research in predicting employee appointments at PT. Mataram Cakra Buana Agung, obtained the result from the C5.0 algorithm or decision tree, which is an accuracy of 90.00%. So it can be concluded that the C5.0 algorithm technique with the decision tree method is considered successful in predicting employee appointments at PT. Mataram Cakra Buana Agung. Keywords: Employee recruitment, classification, C5.0 algorithm.